Associations Between Psychological Capital, Internalizing and Externalizing Problems, Perceived Stress, Emotional, Social, and Psychological Well-Being in Adolescents - Yildirim, Murat; Batmaz, Hasan; Yildirim-Kurtulus, Hacer; Kurtulus, Emin (SAGE PUBLICATIONS INC, 2025)
This study examined the impact of psychological capital-comprising hope, optimism, resilience, and self-efficacy-on comprehensive mental health, defined by the dual criteria of the absence of psychopathological symptoms and the presence of positive functioning. The participants of the study included 429 (65.5% female) Turkish adolescents, ranging in age from 13 to 18 years (M = 16.17 +/- 0.83), and completed self-report measures of psychological capital, mental health, and well-being. Hierarchical regression analysis revealed that hope and optimism showed significant effects on internalizing problems, externalizing problems, perceived stress, emotional well-being, social well-being, and psychological well-being, even after accounting for the influence of age and gender. Additionally, resilience and self-efficacy demonstrated significant effects on psychological well-being. These results suggest the important role of psychological capital in enhancing psychological functioning and provide further evidence of its impact on the mental health and well-being of adolescents.
Keywords: psychological capital; internalizing and externalizing problems; perceived stress; emotional well-being; social well-being; psychological well-being; MENTAL-HEALTH-CONTINUUM; FORM MHC-SF; LIFE SATISFACTION; DEVELOPMENTAL TRAJECTORIES; POSITIVE AFFECT; SELF-EFFICACY; HOPE; CHILDHOOD; DISORDERS; OPTIMISM; Social Issues; Social Sciences - Other Topics; Sociology